Consensus on potential interventions for improving glycaemic control among patients with type 2 diabetes in Kinshasa, Democratic Republic of the Congo: a Delphi study - Jean-Pierre Fina Lubaki; Olufemi Babatunde Omole; Joel Msafiri Francis (Taylor & Francis Group, 2023)
Background Poor glycaemic control is a multifactorial and complex problem with dire clinical and economic implications. In the Democratic Republic of the Congo, recent studies have shown alarming poor control rates. There is no policy framework to guide corrective actions. Objectives To build a consensus on interventions to improve glycaemic control among patients with type 2 diabetes in Kinshasa, Democratic Republic of the Congo. Methods This was a two-round electronic Delphi study involving 31 local and 5 international experts. The experts rated proposed interventions from previous studies on glycaemic control in sub-Saharan Africa and Kinshasa on a 4-Likert scale questionnaire. Additionally, the experts were asked to suggest other recommendations useful for the purpose. The mode, mean and standard deviation of each statement were calculated for each round. Results Participants reached consensus in five domains that included 39 statements on how to improve glycaemic control in Kinshasa: strengthening the health system, enhancing the awareness of diabetes, alleviating the financial burden of diabetes, enhancing the adoption of lifestyle modifications, and reducing the proportion of undiagnosed diabetes. Conclusions Improved glycaemic control needs to be considered within the broader framework of managing noncommunicable diseases in a more integrated, coordinated and better financed healthcare system. Further studies are needed to operationalise the interventions identified for successful implementation.